Pengaruh Edukasi Gizi Menggunakan Media Puzzle terhadap Peningkatan Pengetahuan dan Niat Terkait Konsumsi Sayur dan Buah pada Anak Sekolah Dasar Negeri Dupak I Surabaya - Sutrisno, Mauline Afifah Putri; Mahmudiono, Trias (Media Gizi Kesmas, 2024)
Background: The level of vegetable and fruit consumption in Indonesia is generally still low at 95.5%. Children who consume small amounts of vegetables and fruits have the potential to suffer from malnutrition. One of the age groups that are vulnerable to nutrition is school children. Objectives: The purpose of this study was to determine the effect of nutrition education using puzzle media on increasing knowledge and intentions related to vegetable and fruit consumption in Dupak 1 Surabaya Elementary School children. Methods: This type of research was a quasi-experiment using pre-post test design. The research sample used was 44 people (22 students in the treatment group and 22 students in the control group) taken randomly with sample random sampling. Data collection in this study used knowledge questionnaires, Theory of Planned Behavior constructs, and intentions. The statistical tests used in this study were Paired T-Test and Independent T-Test. Results: Paired T-Test analysis revealed that all variables had significant differences in the control group and treatment group. The Independent T-Test analysis showed that there were differences in attitude changes (p=0.004) and subjective norms (p=0.025) between the treatment group and the control group. Providing education using puzzle media was effective in changing attitudes and subjective norms of respondents. Conclusion:  In conclusion, there was a significant increase in the variables of knowledge, attitude, subjective norms, perception of behavioral control, and intention before and after being given nutrition education related to vegetables and fruits in both groups. Providing education with puzzle media was effective in changing attitudes and subjective norms in respondents when compared to poster media.